Operational performance and losses in mechanized soybean harvesting as a function of field shape - Segatto Strini Paixão, Carla; Damasceno, André Ferreira; Voltarelli, Murilo Aparecido; Spaggiari Alcântara, Aline; Pereira da Silva, Rouverson (Comunicata Scientiae, 2019)
Information on the capacity, operational efficiency, and performance of the harvester is very important in the management of agricultural mechanized systems, influencing decisions made with the aim of optimization. This study aimed to evaluate times, movements, and quality of mechanical soybean harvest operations in different shapes of the plots. Operational performance parameters of the harvester and variables representative of the agronomic aspects of the crop were used as indicators through statistical process control tools. Mechanized harvesting was carried out at a farm located in Uberaba, Minas Gerais, and the experimental design was completely randomized, with 18, 28, and 24 repetitions in irregular, rectangular, and trapezoidal fields, respectively. The activities of the harvester (harvest, unloading, handling, and climate charts) were monitored. The indicators of quality for harvester performance were: forward speed, engine and cylinder rotation and concave opening. The losses were determined: on the platform, internal mechanisms, total and in relation to productivity. The managerial efficiency and shunt time presented better results for the trapezoidal and rectangular section, respectively. All quality indicators evaluated were within the limits of statistical control, characterizing quality and reliability of the soybean harvesting operation.